An Overview on Existential Threats Posed-by Human-like Super-intelligent Machines to Humanity - Jie, Xi (INTI International University, 2021)
This review paper aims to discuss the possibilities a future with human-like super-intelligent machines holds. This paper is done based on a study of secondary data from research papers in the field of history and philosophy. This paper projects that Artificial Intelligence (AI) may hold quality superintelligence, speed superintelligence, and collective superintelligence over us. A forecast based on human history gave us a bleak outlook into the future in which humanity is replaced and wiped out by AIs. Towards the end of the paper, cyborgification is briefly considered as a solution.